Chemical Profile and Biological Activities of Brassica rapa and Brassica napus Ex Situ Collection from Portugal - Carmo Serrano; M. Conceição Oliveira; V. R. Lopes; Andreia Soares; Adriana K. Molina; Beatriz H. Paschoalinotto; Tânia C. S. P. Pires; Octávio Serra; Ana M. Barata (Foods, 2024)
This study aimed to analyse the chemical profile and biological activities of 29 accessions of Brassica rapa (turnips) and 9 of Brassica napus (turnips and seeds) collections, maintained ex situ in Portugal. HPLC-HRMS allowed the determination of glucosinolates (GLS) and polyphenolic compounds. The antioxidant and antimicrobial activities were determined by using relevant assays. The chemical profiles showed that glucosamine, gluconasturtiin, and neoglucobrassin were the most abundant GLS in the extracts from the turnip accessions. Minor forms of GLS include gluconapoleiferin, glucobrassicanapin, glucoerucin, glucobrassin, and 4-hydroxyglucobrassin. Both species exhibited strong antioxidant activity, attributed to glucosinolates and phenolic compounds. The methanol extracts of Brassica rapa accessions were assessed against a panel of five Gram-negative bacteria (Enterobacter cloacae, Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica subsp. enterica serovar, and Yersinia enterocolitica) and three Gram-positive bacteria (Bacillus cereus, Listeria monocytogenes, and Staphylococcus aureus). The extracts exhibited activity against S. enterica and S. aureus, and two showed inhibitory activity against E. coli and Y. enterocolitica. This study provides valuable insights into the chemical composition and biological properties of Brassica rapa and Brassica napus collections in Portugal. The selected accessions can constitute potential sources of natural antioxidants and bioactive compounds, which can be used in breeding programs and improving human health and to promote healthy food systems.